Evaluasi Kinerja Keuangan PT Telkom Indonesia Tbk Berdasarkan Rasio Keuangan - Agusanto Pala’langan; Angelica Tonapa; Stella Nirmala M. Mangampa (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2026)
This study aims to evaluate the financial performance of PT Telkom Indonesia (Persero) Tbk during the period 2020–2023 using the Du Pont System approach and to analyze the impact of community service activities on improving partners’ understanding of financial performance analysis. The research employs a descriptive quantitative method using secondary data derived from the company’s annual financial statements, while the community service impact is assessed through pre- and post-activity surveys. The results indicate that the company’s financial performance experienced fluctuations in Net Profit Margin, Total Asset Turnover, and Return on Equity during the study period. These fluctuations reflect the dynamics of the company’s ability to manage profitability, asset efficiency, and equity utilization. The survey results show a significant improvement in partners’ understanding of financial performance concepts, the application of the Du Pont System, and Return on Equity analysis after the implementation of the program. The findings suggest that the Du Pont System is an effective tool for comprehensive financial performance evaluation, and the community service activities successfully enhanced partners’ analytical capabilities. This study is expected to contribute academically to financial performance literature and practically to the development of financial statement analysis skills.